Deciphering papal ciphers from the 16th to the 18th Century. Issue 6 (2nd November 2021) - Lasry, George; Megyesi, Beáta; Kopal, Nils
Abstract: In Meister's 1906 landmark study, "Die Geheimschrift im Dienste der päpstlichen Kurie von ihren Anfängen bis zum Ende des XVI Jahrhunderts", the 16th Century papal cryptographic service is described as a vibrant, highly professional organization, at the forefront of the science of cryptography in the Late Renaissance. In his work from 1993, Alvarez concluded that by the 19th Century, "the reputation of papal cryptography, once so lustrous, has sadly faded." However, until now, very little was known about the evolution of papal cryptography from the 16th to the 18th Century. In this article, we describe how we obtained a large collection of original papal ciphertexts from the Vatican archives, transcribed them, and how we were able to recover most of the keys, and to decipher the original plaintexts using novel cryptanalysis methods and the open-source e-learning CrypTool platform. The recovered keys and decipherments provide unique insights into papal cryptographic practices from the 16th to the 18th Century. The 16th Century is characterized by innovation and a high level of sophistication, with a primary focus on cryptographic security. From the 17th Century, only the simpler but also less secure forms of ciphers remain in use, and papal cryptography significantly lags behind other European states.